Scrub and Spleen: Scrub Typhus with a Splenic Infarct - Cynthia Amrutha Sukumar; Arya R. Poduval; Nandakrishna Bhat; Sudha Vidyasagar (Indian Journal of Medical Specialities)
Scrub typhus is a mite-borne infection endemic in India. Among the spectrum of complications associated with this tropical illness are manifestations such as encephalitis, acute respiratory distress syndrome, myocarditis, hepatomegaly, splenomegaly, and pancreatitis. Although splenomegaly is a known association among the gastrointestinal complications, splenic infarcts are sparsely reported in the literature. This case is about a woman with scrub typhus who presented with unexplained pain abdomen which was diagnosed as a splenic infarct.